2017
DOI: 10.1007/978-1-4939-7477-1_2
|View full text |Cite
|
Sign up to set email alerts
|

Role of Heat Shock Factors in Stress-Induced Transcription

Abstract: Heat shock proteins (HSP) are rapidly induced after stresses such as heat shock and accumulate at high concentrations in cells. HSP induction involves a family of heat shock transcription factors (HSF) that bind the heat shock elements of the HSP genes and mediate transcription in trans. We discuss methods for the study of HSP binding to HSP promoters and the consequent increases in HSP gene expression in vitro and in vivo. Keywordsheat; shock; factor; binding; transcription (1) IntroductionHeat shock factor (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 44 publications
2
14
0
Order By: Relevance
“…However, Inmt showed an opposite trend in vivo and in vitro, which warrants further research by increasing samples size and technique repeats. The expression of Hspa1b first increased and then decreased slightly at H60 and H120, which is consistent with other HSP family expression levels under HS [51] ( Figure 9D). The relative protein level of Atp5f1 in HS groups was all higher (P < 0.01) than that in control groups ( Figure 9D) and combined with the expression level of Atp5f1 gene at H60 and H120 conditions ( Figure 9C), demonstrating that HS has a delayed effect on the expression of proteins.…”
Section: Confirming the Variation Of Hspa1b Atp5f1 And Inmt As Welsupporting
confidence: 88%
See 1 more Smart Citation
“…However, Inmt showed an opposite trend in vivo and in vitro, which warrants further research by increasing samples size and technique repeats. The expression of Hspa1b first increased and then decreased slightly at H60 and H120, which is consistent with other HSP family expression levels under HS [51] ( Figure 9D). The relative protein level of Atp5f1 in HS groups was all higher (P < 0.01) than that in control groups ( Figure 9D) and combined with the expression level of Atp5f1 gene at H60 and H120 conditions ( Figure 9C), demonstrating that HS has a delayed effect on the expression of proteins.…”
Section: Confirming the Variation Of Hspa1b Atp5f1 And Inmt As Welsupporting
confidence: 88%
“…Genes 2020, 11, x FOR PEER REVIEW 16 of 23 H120, which is consistent with other HSP family expression levels under HS [51] ( Figure 9D). The relative protein level of Atp5f1 in HS groups was all higher (P < 0.01) than that in control groups ( Figure 9D) and combined with the expression level of Atp5f1 gene at H60 and H120 conditions ( Figure 9C), demonstrating that HS has a delayed effect on the expression of proteins.…”
Section: Confirming the Variation Of Hspa1b Atp5f1 And Inmt As Welsupporting
confidence: 86%
“…A unifying factor across all heat shock proteins is HSF-1, the master regulator of the heat shock response in eukaryotes (Gomez-Pastor et al, 2018); which was demonstrated to be essential for thermos-tolerance in mammalian systems using a targeted genetic approach (McMillan et al, 1998). The HSF family of transcription factors (HSF1-6 in humans) appears to not only drive the various heat shock proteins but also induce a concerted array of stress response genes that respond to a variety of stimuli, including heat, oxidative stress, metals and proteotoxicity (Murshid et al, 2018). In response to stress, inactive monomeric HSF-1 is activated resulting in formation of a DNA-binding homotrimer via leucine-zipper domains.…”
Section: Heat Shock Proteins: With a Little Help From My Chaperonesmentioning
confidence: 99%
“…CqHsf13 and CqHsf14 belonging to the A4 subgroup had relatively high expressions in all five organs, which was also reported in other plant species [35]. For example, the AtHsfA1 in arabidopsis, and MdHsfA1a, MdHsfA1d, MdHsfB1a in apple as well as HsfA1 and HsfA8 genes in wheat were found to be constitutive expression in the tested organs [36][37][38]. The high expression of CqHsf genes in most tissues indicates that these heat shock transcription factors might be widely involved in the growth and development processes.…”
Section: Expression Patterns Of Cqhsfs In Different Tissues or Organsmentioning
confidence: 51%
“…It is well known that the expression levels of Hsf genes are significantly affected by heat and other stresses in plants [16,38]. In this study, we also analyze the expression profiles of CqHsf genes under various stress conditions to identify the stress-responsive candidates.…”
Section: Expression Patterns Of Cqhsf Genes Under Abiotic Stress Condmentioning
confidence: 99%